1994
DOI: 10.1210/endo.135.4.7925094
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of continuous infusion of interleukin-1 and interleukin-6 on the hypothalamic-hypophysial-thyroid axis.

Abstract: The cytokines interleukin-1 (IL-1) and IL-6 are thought to be important mediators in the suppression of thyroid function during nonthyroidal illness. In this study we compared the effects of IL-1 and IL-6 infusion on the hypothalamus-pituitary-thyroid axis in rats. Cytokines were administered by continuous ip infusion of 4 micrograms IL-1 alpha/day for 1, 2, or 7 days or of 15 micrograms IL-6/day for 7 days. Body weight and temperature, food and water intake, and plasma TSH, T4, free T4 (FT4), T3, and corticos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…However, acute injection of cytokines failed to induce NTIS like features, except for interferon gamma (IFNg) which reduces serum T 3 and T 4 (Boelen et al 1995). Chronic infusions with IL1 and IL6 on the other hand mimick certain symptoms such as decreased serum T 4 and T 3 and decreased thyrotropinreleasing hormone (TRH) expression in the hypothalamus in mice (van Haasteren et al 1994), while chronic IL1b infusions mimicks certain aspects of NTIS in the rat (Hermus et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…However, acute injection of cytokines failed to induce NTIS like features, except for interferon gamma (IFNg) which reduces serum T 3 and T 4 (Boelen et al 1995). Chronic infusions with IL1 and IL6 on the other hand mimick certain symptoms such as decreased serum T 4 and T 3 and decreased thyrotropinreleasing hormone (TRH) expression in the hypothalamus in mice (van Haasteren et al 1994), while chronic IL1b infusions mimicks certain aspects of NTIS in the rat (Hermus et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The continuous IL-6 intraperitoneal infusion (15 mg/day for 7 consecutive days) in rats was associated with a transient decrease in serum T4 and TSH, although less than that caused by IL-1 [145]. In latter study, pro-TRH mRNA hypothalamic and pituitary TSH-b mRNA were unaffected by IL-6, suggesting that the effects of IL-6 on TSH might not necessarily be associated with a decreased synthesis of thyrotropin [145]. On the other hand, the observation that the intracerebroventricular IL-6 administration to rats was followed by a decrease in serum TSH and an increase in serum adrenocorticotropin (ACTH) concentrations, while these changes could be reproduced in hemipituitaries only for ACTH, but not for TSH, suggested that the action of IL-6 on TSH might be exerted predominantly at the hypothalamic levels [146].…”
Section: Others Adipokinesmentioning
confidence: 89%
“…Changes in serum thyroid hormone concentrations could effectively be ascribed to IL-6, since they could be prevented by IL-6 preincubation with its neutralizing antibody [144]. The continuous IL-6 intraperitoneal infusion (15 mg/day for 7 consecutive days) in rats was associated with a transient decrease in serum T4 and TSH, although less than that caused by IL-1 [145]. In latter study, pro-TRH mRNA hypothalamic and pituitary TSH-b mRNA were unaffected by IL-6, suggesting that the effects of IL-6 on TSH might not necessarily be associated with a decreased synthesis of thyrotropin [145].…”
Section: Others Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, now it is well known that IL-1, IL-6 and TNF-α could play central role in the pathogenesis of non thyroidal illness (NTI) syndrome by acting on hypothalamus pituitary-thyroid axis [13] . IL-1, IL-6 and TNF-α are effect as suppressor mediators on thyroid hormones during NTI [14] . Also, Bartalena et al [15] tested that hypothesis in rats with induced hypothyroidism by administration of the methimazole throughout 3 weeks and they concluded that 48 hours after a single dose recombinant human IL-6 injection could reduce serum T3, T4 and TSH concentrations due to central effects of the cytokine.…”
Section: Kandir Keski̇nmentioning
confidence: 99%